FASILITAS OBJEK WISATA PADA DESA PARIANGAN KABUPATEN TANAH DATAR - Martia Gustika; Febri Yuliani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
ABSTRACT The tourism object of Pariangan Village is a village located in Pariangan District, Tanah Datar Regency, West Sumatra Province which is quite well-known and has the potential to become a tourist village destination as well as a place where domestic and foreign tourists from various regions can see first hand the traditional Minangkabau specialties. still adhere to the tradition until now. There is potential in the village. Development of Pariangan Village Facilities. The government and other institutions want to improve the facilities in the village so that they are more optimal in the process so that tourists will get their own satisfaction so that they can increase the number of tourist visits. This study aims to find out how to find out the constraints, conditions and management plans in the tourism object facilities of Pariangan village. This study used descriptive qualitative method. Concept This study uses the theory of facilities. In collecting data, researchers used interview techniques, observation, documentation using key informants and supporting sources as data information. The subjects of this study were the Head of Tourism, Youth, Sports and Tourism of Tanah Datar Regency and Pokdarwis. Analysis of the research data was carried out by reducing data, presenting data, and drawing conclusions. Keywords: Facilities and Tourism Objects of Pariangan Village